POTENTIAL OF METAL PHYTOMINING IN DAGO PAKAR DAILY RESERVOIR POND (DRP) SEDIMENT USING VETIVERIA ZIZANIOIDES AND CYPERUS SP. PLANTS. - Zulfan Muamar, Zaydan
The Cikapundung River is utilized as an energy source by the Bengkok Hydropower Plant. The Bengkok Hydropower Plant, which is equipped with the Dago Pakar Daily Reservoir Pond (DRP), is constrained by the reduced reliability of upstream units due to land changes and decreased water quality resulting in the accumulation of sediments contaminated with heavy metals and potentially polluting the environment. An innovation in extracting low metal content in soil using plants is phytomining. This study aims to determine metal accumulation and potential application of phytomining using hyperaccumulator plants. The selected plants are Vetiveria zizanioides and Cyperus sp. grown on a laboratory scale in three different treatments, namely control treatment (sediment), NPK treatment, and soil mixture treatment. Sediment samples after preparation and characterization of various physico-chemical parameters were then divided into six different reactors to be used as planting media. Plant growth was observed by measuring plant height once a week. After five weeks, the plants were harvested and tested for accumulated metal concentrations in each plant tissue and growing media using an Atomic Absorption Spectrophotometer (AAS). The results showed that Vetiveria zizanioides was able to accumulate Fe, Cu, and Zn metals with the highest concentration in the NPK treatment with consecutive values of 2334.51 mg kg-1 , 53.03 mg kg-1 , and 569.07 mg kg-1 . Fe and Cu accumulation in Cyperus sp. had the highest concentration in the NPK treatment with the results of 2900.07 mg kg-1 and 168.84 mg kg-1 , respectively, while in Zn metal the highest concentration was in the control reactor (sediment) with a value of 529.680 mg kg-1 . The soil mixture treatment gave the greatest increase in plant height and dry weight gain in Vetiveria zizanioides, while the NPK treatment in Cyperus sp. gave the greatest increase in height, dry weight, and metal accumulation compared to other treatments. BCF analysis showed that Vetiveria zizanioides had better accumulator ability on Zn metal, while Cyperus sp. better accumulated Fe and Cu metals. TF analysis showed that the phytoextraction process occurred in the NPK treatment in Vetiveria zizanioides for Zn metal with a value of 1.056 and Cyperus sp. for Cu metal with a value of 3.767. TF values other than these values obtained a value of <1 which indicates that most of the metal is still accumulated in the root vacuole so that little is translocated to the crown. This study also found that Vetiveria zizanioides can produce as much as 2409.551 kg/hectare of biomass with the highest potential accumulation of Zn metal reaching 2.341 kg/hectare.year, while using Cyperus sp. can produce as much as 2378.203 kg/hectare of biomass with the highest potential accumulation of Fe metal reaching 62.073 kg/hectare.year and Cu metal reaching and Cu metal of 3.614 kg/hectare.year.